Treatment and bioenergy recovery from livestock wastewater in UASB reactor: novel approaches for engineering projects - Vieira de Mendonça, Henrique; Silva dos Santos, Mônica (Revista Brasileira de Engenharia de Biossistemas, 2025)
This study presents an innovative approach for energy recovery and treatment of cattle wastewater, exploring the performance of a UASB reactor operated at 40°C, a condition that has received scant attention in the extant literature. The experiment was conducted using a semi-continuous feeding regime, with hydraulic retention times of 6, 5, 3, and 2 days, and organic loading rates of 4, 5, 7, and 11 kg COD m-3 d-1. The range of organic matter removal for total COD was 60% to 80%, and for soluble COD, it was 50% to 75%. These values resulted in methane yields ranging from 0.20 to 0.34 m³ CH4 per kilogram of total COD removed and from 0.4 to 0.5 m³ CH4 per kilogram of soluble COD removed. The findings underscore the efficacy of operating the reactor under these conditions, not only in achieving substantial biogas production but also in ensuring the efficient removal of organic matter. This reinforces the potential of the processes as a sustainable and effective alternative for treating effluents with high pollutant loads, thereby combining environmental mitigation and clean energy generation.